The effect of HIV and the modifying effect of antiretroviral therapy on body-mass index and blood pressure levels in rural South Africa - Andrea B Feigl, MPH; Frank Tanser, PhD; Till W Bärnighausen, MD (Elsevier, 2014)
Background: The trajectory of body-mass index (BMI) in long-term HIV patients on antiretroviral therapy (ART) compared with the non-HIV population has been poorly studied. Methods: Methods In 2003 and 2010, height, weight, and blood pressure measurements were recorded in a subset (n=505) of the population in KwaZulu-Natal, South Africa-a region with a very high prevalence of HIV (30%) and intensive ART rollout since 2004. Difference analysis was used to study change in BMI and blood pressure over time in HIV-negative patients, HIV-positive patients who had been on ART for 0-<2 years (HIV+ART0-<2 years; n=62), HIV patients who had been on ART for 2-5 years (HIV+ART2-5 years; n=44), and HIV-positive patients who were not on ART (HIV+ART−; n=52). Multinomial logistic regression models were used to assess change in the risk of obesity and hypertension. Findings: The HIV-negative and HIV-positive groups were both overweight at baseline (mean BMI 29·5, 95% CI 28·8-30·3; and 27·5, 25·9-29-3, respectively). The HIV-negative group was obese in 2010 (mean BMI >30); all other groups remained in the overweight range (25< BMI <30). The difference in change in BMI between the HIV-negative and the HIV-positive ART0-<2 years group was −5·21 (95% CI −7·53 to −2·89; p=0·001). This difference in change in BMI was attenuated by increased ART use, with a difference in BMI change between the HIV− and the HIV+ART2-5 group of −1·07 (95% CI −2·5 to 0·361; p=0·086), suggesting a U-shaped association of BMI with ART use. The difference in change in BMI between the HIV+ART− and the HIV+ART0-<2 years group was −4·14 (95% CI −6·76 to −1·53; p=0·002). The HIV+ART− group had the highest average systolic blood pressure in 2003. Compared with the HIV− group, the overall systolic blood pressure in the HIV+ART− group significantly declined by −7·55 mm Hg (95% CI −13·2 to −1.90; p=0·009). The effect of the dose of ART on systolic blood pressure change was not significant (p=0·853). Interpretation: Short-term ART exposure (0-<2 years) was associated with a slight decline in BMI compared with all other populations, because patients are selected into ART on the basis of having advanced HIV disease. Long-term ART exposure (2-5 years) led to a return to a highly overweight BMI and an increased chance of being obese than normal weight by 2010. Funding: None.